Calling the cavalry: firm-level investment in the face of decentralized expropriation. Issue 4 (19th August 2020) - Marques, Israel; Levina, Irina; Kazun, Anton; Yakovlev, Andrei
Abstract: What characteristics of firms give them the confidence to invest in settings rife with expropriation by local officials? Empirically, firms in the developing world often face the threat of expropriation from local agents of the state rather than a centralized autocrat. Because policing local officials is costly, the state cannot easily credibly commit to doing so. This has negative consequences for investment. We argue that one solution is to allow firms to approach the state directly to ask for intervention. Not all firms are equally able to successfully get the attention of the state, however, so this mechanism only works for some. We develop an argument about the firm-level characteristics – large-scale employment, political connections, foreign ownership, and business association membership – that should make the central state more attentive to calls for help. Because firm with these characteristics are more likely to secure intervention against predatory bureaucrats, the latter are less likely to try to expropriate them. These firms' investment decisions should be less sensitive to local expropriation than other firms. We test this argument using data on cases of decentralized expropriation across Russia's regions and firm-level data from a cross-regional, large scale survey of Russian firms.